PENGARUH ADAPTABILITAS KARIR TERHADAP KEPUASAN HIDUP DENGAN KEBERANIAN SEBAGAI PEMEDIASI PADA MAHASISWA S1 FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS SYIAH KUALA - Sulvia Putri; Ade Irma Suryani (Jurnal Manajemen Inovasi, 2019)
AbstractThis study aims to measure the effect of Career Adaptability to undergraduate student’s Life Satisfaction in Economic and Business Faculty of Syiah Kuala University with Courage as mediating variable. The sample used in this study were active undergraduate student’s in odd semester 2018/2019 is totalling 243 respondents. Data collection equipment used in this study was a questionnaire. The sampling technique used is Proportionated Stratified Random Sampling. Hierarchical Linear Modelling (HLM) was used as a method of analysis to determine the effect of all the variables involved.Based on the result of the HLM analysis indicated that Career Adaptability positively influence Life Satisfaction, Career Adaptability positively influence Courage, Courage positively influence Life Satisfaction and Courage mediate the relationship between Career Adaptability and Life Satisfaction. KeywordsCareer Adaptability, Life Satisfaction, Courage, Hierarchical Linear                   Modelling